Using web services to realize remote hearing assessment. - Yao J; Wan Y; Givens GD; Yao, Jianchu; Wan, Yongbo; Givens, Gregg D (Journal of Clinical Monitoring & Computing, 2010)
Background: Internet-based tele-audiology is expected to relieve the dilemma between the lack of resources and high demand of audiological care services. This paper presents a web services based, distributed pure-tone hearing assessment system that improves accessibility of traditionally underserved groups to audiology care.Methods: The system employs browser-server network architecture to connect patients to audiology specialists through a web server where all application software is hosted. Software on the server is designed with a three-tier approach which makes the system scalable to include other audiological services. Hearing test data are stored in a standard database and can potentially be integrated into established electronic medical records. On the remote patient side, off-the-shelf audiometers are adopted. The Internet connection of these audiometers can be flexibly configured either with or without a computer. Two aspects of the system were tested: (1) the clinical effectiveness of the system: double-blinded experiments were conducted to assess hearing ability of 30 subjects and paired t-tests were utilized to compare assessment results from the remote approach and the conventional setup; and (2) to analyze the system bandwidth requirements, data traffic among the server, the audiometer, and the audiologist terminal was examined with a network monitoring software (wireshark).Results: Paired t-test results have demonstrated that the remote hearing assessment is equivalent in effectiveness to its conventional counterparts at all tested frequencies (P values are in the range of [0.12, 0.94]), and the bandwidth required by the system is less than 1 Mbps, falling within the capacity of average commercial Internet service subscription.Conclusions: The project developed a remote hearing assessment system based on services on a web server. The system minimizes hardware and software requirements on the audiologist's computer and can be realized with regular Internet service subscription. Patient operations involved in hearing assessment are simple; making hearing test services more accessible to those otherwise may not be able to obtain the desired hearing care.